Analysis Business Prospect of Metaverse from Meta Company - Faszrul, Faszrul; Adrian Irnanda, Pratama (Politeknik Negeri Sriwijaya, 2024)
Metaverse as an evolution of digital interaction has an important role in life and in the future because it allows people to interact in virtual environments in a more immersive and realistic way. This research aims to find out the product description, business concept, business goals, target market, business risk, marketing strategy, financial statements of Metaverse from meta company so that the public or the worl d of education can get an idea of the business prospects of Metaverse. This study used descriptive qualitative method. Data collection techniques are visual content and documentation. The object of this research is Metaverse technology from meta company. The result of this research is Metaverse a virtual world created to interact with other people immersively without being in the same room by using a VR (Virtual Reality) headset. The Metaverse business concept includes key partners, key activities, value propositions, customer relationships, customer segments, key resources, channels, cost structure, revenue streams. The business goals of Metaverse are to create the digital world, where people can work together, spend time with friends like the real world. These are some of the target markets for the Metaverse, including content developers, Metaverse users, marketers and businesses. Business risks of the Metaverse are competitors and regulatory or political risks. Marketing strategy of Metaverse namely Increase Awareness by disseminating content, Partnerships and sponsorships, and Customer Engagement. Reality Labs reports that Metaverse financial reports experience continuous losses until 2023. Keywords: Metaverse Prospects and Product Description, Business Concept and Business Goals, Target Market and Business Risk, Marketing Strategy and Financial Statements